Ultrasonic defouling of reverse osmosis membranes used to treat wastewater effluents - Feng, D.; van Deventer, J.; Aldrich, Chris (Pergamon, 2006)
On-line ultrasonic cleaning was used to remove fouling from a commercially important polyamide based reverse osmosis membrane during cross-flow filtration of CaSO4, Fe3+ and carboxyl cellulose solutions. In each case, the permeate flux of the membrane increased significantly, with virtually no decrease in rejection in the presence of ultrasonication. Membrane surface characterization via scanning electron microscopy (SEM) confirmed the beneficial effect of ultrasonication on the membrane permeate flux. These studies suggest that ultrasonic defouling may be a very useful approach for the future development of reverse membranes, especially as far as fouling with organic materials is concerned.